Influence of oyster and seaweed cultivation facilities on coastal environment and eukaryote assemblages in Matsushima Bay, northeastern Honshu, Japan - Okumura, Yutaka; Masuda, Yoshio; Matsutani, Minenosuke; Shiomoto, Akihiro (Frontiers in Marine Science, 2023)
The northeastern coast of Japan suffered a massive tsunami in 2011, a natural disaster which ‘reset’ the coastal ecosystem when it destroyed much of the original sealife and scoured the seabed. This has presented an opportunity to learn more about the load on coastal ecosystems exerted by human exploitation such as aquaculture rafts and areas of anchored and float-suspended ropes. We surveyed the coastal environment in Matsushima Bay for approximately four years following the year after the occurrence of the 2011 tsunami. Phytoplankton abundance increased with increasing water temperature. Nutrient concentrations were high at the exit of a small branch of the Ofuna-iri Canal (entering the southwestern inner part of the bay at Shiogama) but no significant differences in nutrient concentrations were observed at other stations, so it is considered that the aquaculture installations in Matsushima Bay currently have no significant effect on observed nutrient concentrations. The composition of eukaryotes in the surface seawater varied with the year and the season, but there were no clear differences between sampling stations. The lack of any differences in nutrient concentrations or eukaryote assemblages between areas with or without aquaculture installations is considered to be a result of efficient seawater exchange, despite the presence of many small islets separating Matsushima Bay from the open ocean. In addition, the aquaculture installations at present number less than half of the maximum number before the tsunami, so the bay is by no means overexploited by aquaculture. It is concluded that the current aquaculture installations have no major negative impact on the environment in Matsushima Bay.